Peptide Nucleic Acids as a Tool for Site-Specific Gene Editing - Ricciardi, Adele; Quijano, Elias; Putman, Rachael; Saltzman, W.; Glazer, Peter (Molecules (Basel, Switzerland), 2018)
Peptide nucleic acids (PNAs) can bind duplex DNA in a sequence-targeted manner, forming a triplex structure capable of inducing DNA repair and producing specific genome modifications. Since the first description of PNA-mediated gene editing in cell free extracts, PNAs have been used to successfully correct human disease-causing mutations in cell culture and in vivo in preclinical mouse models. Gene correction via PNAs has resulted in clinically-relevant functional protein restoration and disease improvement, with low off-target genome effects, indicating a strong therapeutic potential for PNAs in the treatment or cure of genetic disorders. This review discusses the progress that has been made in developing PNAs as an effective, targeted agent for gene editing, with an emphasis on recent in vivo, nanoparticle-based strategies.